Evaluation of Screening Tool of Older Persons’ Prescriptions/Screening Tool to Alert to Right Treatment and Beers Criteria Practice in Geriatric Patients - Arvind, Chauhan Sneha; Deep, Patel; Jamsa, Anas (South Eastern European Journal of Public Health, 2025)
1.INTRODUCTION: Given that seniors make up most drug users, rational drug use is especially important in this population. The growing incidence of pathological medical disorders makes this topic especially important for the healthcare industry. The pharmacokinetic changes and possible susceptibility to specific medications, especially those that influence the central nervous system and can cause adverse drug reactions, cause elderly persons' medication responses to differ. Owing to several comorbidities, older people are more likely to engage in polypharmacy, or the use of five or more medications. This increases the risk of adverse drug reactions (ADRs) and drug interactions, which can lead to inadequate therapy and extended hospital stays. Mark H. Beers created the crucial Beers Criteria in 1991 as a set of recommendations for safe medication prescription in the elderly. Their goals are to identify drugs that should be avoided, limit inappropriate prescribing, and prevent adverse drug reactions (ADRs). To optimise medicine selection, these evidence-based recommendations are applied in all care settings, except for hospice and palliative care. 2. AIM: “Evaluation of Screening Tool of Older Persons’ Prescriptions/Screening Tool to Alert to Right Treatment and Beers criteria practice in geriatric patients.” 3. OBJECTIVE • Assessing Adherence to Beers Criteria Standards in geriatric patients. • To evaluate specific adverse drug responses (ADRs) linked to different prescription regimens used. • To determine the association between number of PIMs prescribed with total number of drugs prescribed. 4. METHOD: Data were gathered from 153 individuals, all of whom were older than 65. and used Google Forms to examine and understand. This study will ascertain the prevalence of PIMs as well as the relationship between the total number of prescription drugs prescribed. 5.RESULT: The study found that 58.16% of patients were male, with 41.83% female. The majority were aged 65-70. The majority were admitted to general medicine, followed by cardiology and pulmonology. Hypertension was the most prevalent condition, followed by ischemic heart disease and type 2 diabetes. A study found that 13.07% of prescriptions were filled with 12 medications, indicating polypharmacy in older patients. Polypharmacy was prevalent (67.02%). Most prescriptions contained 4 or more PIMs; pantoprazole was prescribed to 89.1% of patients being the most prescribed PIMs. Diuretics were prescribed to 46.50% of patients, with furosemide being the most prescribed diuretic. R=0.498 indicates a medium positive association between the quantity of prescription medications and PIMs. 6. CONCLUSION: The fact that every prescription under consideration contained at least one PIM suggested that the hospital's prescribing practices were illogical. This study emphasizes how important it is to make doctors and chemists knowledgeable about standards or criteria, such as the Beers criterion and STOPP/START criteria to practice safer prescribing practices for senior patients.